Forensic Assistance Project: Consultant Report 1999-019 Dvorište I Federation Commission on Missing Persons - Bosniak Side - Physicians for Human Rights
Forensic report on individual and mass grave exhumations in Bosnia and Hercegovina created during the Forensic Assistance Project (FAP). The report was authored by: Harrington, Richard On 25 May 1999 the Federation Commission on Missing Persons - Bosniak Side conducted a recovery operation of surface-scattered human remains near a highway tunnel entrance between Goražde and Višegrad. The partial skeletal remains of what appeared to be a single adult male were scattered over a small area approximately 10 m from the highway and 1 km east of the town of Dvorište. Some of the skeletal elements had been dispersed down the steep slope toward the Drina River, but were recovered; the skull, which was not found, could have rolled into the river. The remains reportedly belonged to the father of one of the witnesses who assisted in the recovery. Features of the skeletal remains were consistent with this witness's description of his father's age, stature, and other traits. The individual being searched for was Ejub Dervišević, a 53-year-old Bosniak soldier who was reportedly killed in the area on 31 May 1993. Place of Exhumation: Dvorište Date of Exhumation: 25 May 1999 Minimum Number of Exhumed Individuals: 001